SISTEM INKUBASI KEWIRAUSAHAAN YANG TERINTEGRASI UNTUK MEWUJUDKAN PROGRAM JEMARI (JOGOTIRTO MANDIRI BERDIKARI) - Yusqi Mahfuds; Fany Rizki Nurfadilah; Inayah Inayah; Risma Oktaviana Pratiwi (Jurnal Abdi Insani, 2022)
The residents of Jogotirto Village are looking for various types of independent businesses such as the agricultural sector, trade, government, and MSMEs. In the era of technological development, the use of social media marketing (SMM) is the most important choice that business people can make to continue. Unfortunately, there are still many MSME actors in Jogotirto who do not understand the article on social media for marketing. In addition, existing MSME organizations also do not have mature activities and organizations. Therefore it is important to carry out a solution through entrepreneurial incubation. In this study, the author aims to find out the problems that occur for implementing SMEs in Jogotirto Village, and from the problem, it will be studied to find a solution. So that from this solution, it will later be able to contribute to the implementers of MSMEs in Jogotirto Village. To facilitate this research, here the author uses a qualitative approach that relies on the process and techniques of data collection using interviews, observation, and literature study. This study concluded that the entrepreneurial incubation named JEMARI (Jogotirto Mandiri Berdikari) could be a solution to improve MSME skills and organizational development. This incubation system is carried out through various activities such as mapping and grouping, training, mentoring and monitoring the entrepreneurial community. Activities carried out: Mapping Potential and MSMEs, socialization with the management of the Jogotirto MSME Communication Forum, organizational training, digital marketing training, assistance through social media. Initial calculations and planning were carried out by Sleman Youth Fighters, with the aim of forming community incubation from the final stage to the mentoring/observation stage, with location and basic training